ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MTs PADA MATERI LINGKARAN - neng hanipah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to describe the ability of mathematical creative thinking of students of class IX on the material of the circle. The method used a descriptive research method. The type of research used in this research is qualitative research. The subject is a student of class IX MTs in Bandung as many as 32 students. Data collection techniques are in use is to test the ability of creative thinking in the form of essay. Research results can be concluded that indicators of flexible thinking ability (Flexibility) that is capable of providing ideas, questions or the answers vary with the percentage of 81,%; original thinking ability indicators (Originality) that is able to give new expression to the unique ideas and with a percentage of 70%; An indicator of ability to think Fluently (Fluency) that is capable of generating ideas, answers, troubleshooting or questions smoothly amounted to 55%; original thinking ability indicators (Originality) that is able to give new expression and unique ideas of 61% and an indicator of the ability of Thinking elaboration (Elaboration) that is able to itemize and develop an object of 26%.